Numerical study of fluid-structure interaction in supersonic regimes: Flat panel mouvement in a super-sonic fluid flow - Giordano, Jérome; Burtschell, Yves; Medale, Marc; Perrier, Pierre (European Journal of Computational Mechanics, 2004)
A numerical model of fluid-structure interaction has been developed. This numerical model allowed us to find the resonance phenomenon of the movement of an aluminium plate subjected to an eulerian supersonic flow on one of its faces. FFT of significant variables allow us to give an estimation of critical Mach number and pulsation, validated by an analytical model. Frequently neglected in the literature, an extension for the viscous fluid flow case is proposed. Thus, the plate movement amplification due to boundary layer detachment has been shown. An estimation of critical Mach number and pulsation has been given in this case, too.